Fragmented mnemonics : an investigation into contemporary jewellery as means of externalizing memory - Groenewald, Joani (Stellenbosch : Stellenbosch University, 2015)
ENGLISH ABSTRACT: This thesis interrogates my own memory in order to illustrate its fragmented and unstable nature. I revisit a specific childhood memory and attempt to recreate it visually through the creation of jewellery pieces. However, the unattainability of a consistent memory becomes increasingly evident in the process of its externalization. My work thus speaks of the unravelling of memory, as well as the piecing together and imagining of a new memory. This thesis and my practical work are an exploration of this ambivalent nature of memory. Even though memory is concerned with the past, it is also about the present as our memories can also be manipulated by present prejudices.